2017
DOI: 10.1111/jopr.12641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gingival Retraction Paste and Subsequent Cleaning with Hydrogen Peroxide on the Polymerization of Three Elastomeric Impression Materials: An In Vitro Study

Abstract: Under these in vitro conditions, it can be concluded that the remnants of Expasyl on specimens caused a significant polymerization inhibition of the 3 impression materials tested. Subsequent cleaning with 3% H O significantly reduced this inhibitory effect on polymerization. Expasyl should not be used with Monophase polyether material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…70% were aware of Expasyl paste which is used in retraction requires minimal time and force when compared to retraction cord. Abduljabbar and Al Baker found similar results to our study where he mentioned the impact of expasyl in gingival retraction paste on bond strength of self-etch and total-etch systems (Al Baker et al, 2015;Abduljabbar et al, 2019).66% were aware of Comprecap , livaditis in his study observed the same results of our study (livaditis, 1998).…”
Section: Resultssupporting
confidence: 89%
“…70% were aware of Expasyl paste which is used in retraction requires minimal time and force when compared to retraction cord. Abduljabbar and Al Baker found similar results to our study where he mentioned the impact of expasyl in gingival retraction paste on bond strength of self-etch and total-etch systems (Al Baker et al, 2015;Abduljabbar et al, 2019).66% were aware of Comprecap , livaditis in his study observed the same results of our study (livaditis, 1998).…”
Section: Resultssupporting
confidence: 89%
“…In a clinical scenario, a minimum crevicular width of 0.2-0.3 mm is required to capture the preparation margins and the area beyond for durability of the impression recorded and the ability to remove and pour. 6,24 A known criterion for polymerization inhibition evaluation was employed, as its validity has been verified in multiple previous studies. 6,11,21,22 The three categories (Table 1) of un-polymerized impressions were presented to demonstrate the severity of polymerization inhibition; however, all three categories were considered inhibited impressions as they cannot be recommended as successful impressions clinically.…”
Section: Discussionmentioning
confidence: 99%
“…6,24 A known criterion for polymerization inhibition evaluation was employed, as its validity has been verified in multiple previous studies. 6,11,21,22 The three categories (Table 1) of un-polymerized impressions were presented to demonstrate the severity of polymerization inhibition; however, all three categories were considered inhibited impressions as they cannot be recommended as successful impressions clinically. To standardize impressions among the three evaluators, inter-and intra-examiner reliability was assessed using some pilot tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations